ChemInform Abstract: Copper‐Catalyzed Aerobic Oxidative Decarboxylative Amination of Arylacetic Acids: A Facile Access to 2‐Arylquinazolines. Issue 34 (4th August 2016) - Yan, Yizhe; Shi, Miaomiao; Niu, Bin; Meng, Xiangping; Zhu, Changrui; Liu, Gengyao; Chen, Ting; Liu, Yanqi
Abstract: 30 examples